Taktik Pengaruh dalam Kepemimpinan - Maulan Aklil (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2025)
Leadership in modern organizations has undergone a significant paradigm shift. No longer solely understood as a formal power inherent in a structural position, leadership is now examined as an interpersonal process that is complex, dynamic, and full of nuances of influence. In an increasingly horizontal, collaborative, and network-based organizational environment, a leader's effectiveness is not only determined by formal authority, but also by his ability to influence others strategically and ethically. There are nine main tactics used by leaders to influence the behavior and decisions of others: legitimacy, rational persuasion, inspirational pleas, consultation, exchange, personal pleas, ingratiation, pressure, and coalition. This study explores these nine influence tactics, using an exploratory qualitative approach through document studies and narrative analysis.  The results show that the influence tactics carried out by the Leader must be effective and able to adapt the tactics to the social context and ethical values. Influence tactics in carrying out leadership are not prohibited but must be done responsibly and elegantly.